KAJIAN TINGKAT IMPLEMENTASI DAN HAMBATAN PENGGUNAAN BUILDING INFORMATION MODELLING (BIM) - Candra Christianti Purnomo; Lolom Evalita Hutabarat; Ruth Putri Wina Gultom (UKI Press, 2022)
Building Information Modeling (BIM) is essential for the construction sector, especially in Indonesia, because it simplifies challenging tasks, boosts stakeholder participation, and improves overall results. Only state-owned contracting businesses were involved in BIM implementation's adoption and digitization phase in 2017. Since 2015, Singapore has developed and integrated BIM into construction projects, resulting in widespread technology usage. Human resource readiness with technology, preferences for the old system (considered easier to manage and less dangerous), malfunctioning equipment, and a lack of personal motivation are among the factors driving the acceleration of BIM adoption in the Indonesian construction services industry. In optimizing information technologies in the construction sector, each planning element must submit building plans using BIM, including architecture, civil engineering, and electrical engineering. It seeks to boost productivity and collaboration to compete globally with constricted workflows. It is crucial that the Indonesian construction services industry adopt BIM, define implementation standards for BIM, and foster industry cooperation. Building a BIM implementation system in a corporation is challenging since socializing and altering the method and rhythm of work using BIM could take up to two years.